Implementasi Parenting Islami dan Pembelajaran Al-Qur’an melalui Program Madrasah Sabtu Ceria - Tammam Sholahudin; Muhammad Zulfahmiansyah; Namira Salsabila Wibowo; Triono Ali Mustofa (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program was implemented in response to the low level of Qur’anic literacy and limited maternal involvement in children’s religious education in Kampung Gondang, Surakarta. The “Madrasah Sabtu Ceria” program aims to reconstruct the role of mothers as Madrasatul Ula through the integration of Qur’anic literacy learning (BTA) for children and Islamic parenting education for mothers. The program was carried out through three main stages: community socialization to residents of Kampung Gondang, Islamic parenting counseling sessions (penyuluhan) for mothers through weekly study circles, and direct Qur’anic literacy mentoring (pendampingan) for children conducted every weekend. The outcomes of this community service reveal a significant increase in maternal involvement, children’s Qur’anic literacy, and the transformation of religious character and family culture. The synergy between TPA and family environments strengthens the internalization of religious values.